Functional outcome of varus derotation osteotomy in late presenting Perthes disease: a case series - Nama, K. G.; Bansal, Aakash; Mantri, Nihit; Meena, R. P.; Joshi, Sachin (International Journal of Research in Orthopaedics, 2025)
Late-onset Perthes disease, particularly in children older than nine years, is known to have a more aggressive course and a less favorable prognosis, often progressing to osteoarthritis by the fourth decade of life if left untreated. While younger children are usually managed conservatively, and those aged 6-9 years may benefit from surgical intervention, the optimal treatment strategy for children aged 8 years and above remains controversial. This case series evaluates the clinical and radiological outcomes of varus derotation osteotomy (VDRO) in 12 children (10 males, 2 females) with a mean age of 9.4 years, treated at the Department of Orthopaedics, Government Medical College, Kota, between 2020 and 2025. All patients were classified as stage IB, IIA, or IIB based on the modified Elizabethtown classification and presented with restricted hip abduction and internal rotation. Hip pain was reported in 58.33% of cases, and 75% had a limp. VDRO was performed approximately three weeks after diagnosis. Five patients (41.67%) were older than 10 years at presentation. Outcomes were assessed at an average follow-up of 3.4 years. Radiological evaluation included the caput index (CI), epiphyseal quotient (EQ), and articulotrochanteric distance, while clinical assessment used range of motion and the Harris Hip Score. Significant improvements were observed in CI (p=0.000) and EQ (mean postoperative value 0.606; p=0.0000). Favorable results were seen in all patients with stage IB and IIA disease, and in 50% of those with stage IIB. VDRO appears to be an effective option for late-presenting Perthes disease in this age group.